2020
DOI: 10.1017/cem.2019.472
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the potential impact of an emergency department extracorporeal resuscitation (ECPR) program: a health records review

Abstract: ObjectivesExtracorporeal cardiopulmonary resuscitation in refractory cardiac arrest (ECPR) is an emerging resuscitative therapy that has shown promising results for selected patients who may not otherwise survive. We sought to identify the characteristics of cardiac arrest patients presenting to our institution to begin assessing the feasibility of an ECPR program.MethodsThis retrospective health records review included patients aged 18–75 years old presenting to our academic teaching hospital campuses with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…Grunau et al found that 10.2% of OHCA patients presenting to Vancouver EDs were eligible for ECPR (10). In Ottawa, a similar study identi ed that 6-15% of their OHCA patients were eligible for ECPR (16). A retrospective study conducted in Saskatoon in 2016 found that 14% of non-survivors of OHCA represented suitable candidates for ECPR (9,15).…”
Section: Discussionmentioning
confidence: 99%
“…Grunau et al found that 10.2% of OHCA patients presenting to Vancouver EDs were eligible for ECPR (10). In Ottawa, a similar study identi ed that 6-15% of their OHCA patients were eligible for ECPR (16). A retrospective study conducted in Saskatoon in 2016 found that 14% of non-survivors of OHCA represented suitable candidates for ECPR (9,15).…”
Section: Discussionmentioning
confidence: 99%
“…Zur Untermauerung unserer Erkenntnisse haben wir sechs systematische [ 164 – 169 ], vier narrative Reviews [ 170 173 ] und 13 Beobachtungsstudien [ 76 , 148 , 168 , 174 183 ] zu diesem Thema gefunden. Andere Quellen wie Kommentare und ethische Dissertationen wurden als indirekte Informationen angesehen.…”
Section: Evidenz Die Den Richtlinien Zugrunde Liegtunclassified
“…Sie urteilten, dass dies machbar ist und sowohl das neurologisch intakte Überleben als auch die Organspende durch Nichtüberlebende erhöhen könnte. Die Implementierung in vorhandene Rettungsdienstsysteme ist eine Herausforderung und erfordert detaillierte Protokolle für die Patientenauswahl und den Transport [ 168 , 181 183 ]. Die Ethik-Autorengruppe stellt fest, dass mehr Forschung zur Patientenauswahl, zu veränderbaren Ergebnisvariablen, zum Nutzen-Risiko-Verhältnis und zur Kostenwirksamkeit der E‑CPR dringend erforderlich ist.…”
Section: Evidenz Die Den Richtlinien Zugrunde Liegtunclassified
“…There have been several recent Canadian studies, evaluating the number of patients eligible for ECPR [ 10 , 15 , 16 ]. Grunau et al found that 10.2% of OHCA patients presenting to Vancouver EDs were eligible for ECPR [ 10 ].…”
Section: Main Textmentioning
confidence: 99%
“…Grunau et al found that 10.2% of OHCA patients presenting to Vancouver EDs were eligible for ECPR [ 10 ]. In Ottawa, a similar study identified that 6–15% of their OHCA patients were eligible for ECPR [ 16 ]. A retrospective study conducted in Saskatoon in 2016 found that 14% of non-survivors of OHCA represented suitable candidates for ECPR [ 9 , 15 ].…”
Section: Main Textmentioning
confidence: 99%